UJI EFEKTIVITAS EKSTRAK ETANOL HERBA KROKOT (Portulaca oleracea L.) SECARA Topical UNTUK Reepitelisasi PENYEMBUHAN LUKA INSISI PADA TIKUS PUTIH (Rattus norvegicus) - Rani Ardiani (Jurnal Penelitian Farmasi & Herbal, 2021)
The krokot is a weed that usually grows in plantations. In scientific language, purslane is called Portulaca oleracea L. Purslane is well-known as a nutritious plant in several countries such as China, Mexico, and Greece. In Indonesia, purslane is also known to have uses, or a substitute for ginseng. This aims of the study to determine the effectiveness of purslane herb ethanol extract ointment on wound healing in white rats. This research was conducted using an experimental method. In this study, phytochemical screening and simplicia characterization were carried out. Incision wound healing effect was tested on 25 male white rats with 5 treatment subgroups, namely positive control, negative control, purslane herb ethanol extract ointment 10%, purslane herb ethanol extract ointment 20%, purslane herb ethanol extract ointment 30%. The ointment base used is Vaseline album, liquid paraffin, and solid paraffin. All formulations of purslane herb 10%, 20% and 30%, met the requirements for evaluation of ointment preparations. Phytochemical screening results showed positive containing flavonoids, tannins and saponins. The results of the characterization of purslane herb simplicia powder obtained water content of 8.37%, water soluble extract content of 11.35%, ethanol soluble extract content of 10.99%, total ash content of 7.46% and acid insoluble ash content of 0.88%. The average results of observation of incision wounds in white rats were concentrations of 10% (22 mm) for 14 days, 20% (0.1 mm) for 14 days, 30% (0.04 mm) for 14 days. While the positive control (betadine ointment) was (0 mm) and the negative control (ointment base) was (0.42 mm). It can be concluded that purslane herb ethanol extract can provide effectiveness and antioxidants for wound healing in white rats. The purslane herb 30% ethanol extract has almost comparable effectiveness with betadine ointment in healing incisional wounds in white rats.